An Investigation of the Row and its Place in Persian Lyric Poems of Ghaleb Dehlavi - Seyed Abrar Hosseini; Abdolghafour Jahandideh (مطالعات زبانی و بلاغی)
A row is one of the elements of classical Persian poetry and as one of the main pillars of lateral music, it plays a major role in classical and ancient Persian poetry and contributes greatly to the melody and soft listening of the poem. In Persian poetry, at first, the row was very weak; but as the poetry evolved and went through different stages of development, the wide usage of the row was observed. One of the poets who paid special attention to ROW and ROW has a high frequency in his poems was Ghalib Dehlavi. In Persian lyric poems of Ghalib Dehlavi, the presence of rows and especially long and difficult rows is prominent. In this article, the row in all Ghalib Persian sonnets has been studied, and by providing accurate statistics, it has been determined that the number of different Ghalib sonnets is much more than his lineless lyric sonnets. The statistics of the types of lines in Dehlavi's Persian sonnets show that a verb-type row comprises more than half of all the lines of his Persian sonnets. On the other hand, the functions of the row in Ghalib Persian lyric poems have also been studied and it has been concluded that functions such as music and melody, row fit with the theme of the poem, accompanying and unifying the audience, integration of thoughts and imaginations of the poet, highlighting a specific image or theme and the richness of the lyric song with the similarity of row and rhyme has been considered by the poet in Persian lyric poems.